Is Workload Associated with Internal Impingement in Professional Baseball Players? An Analysis of Days of Rest, Innings Pitched and Batters Faced (221). Issue 10 (31st October 2021) - Chalmers, Peter; Mcelheny, Kathryn; Dangelo, John; Ma, Kevin; Rowe, Dana; Erickson, Brandon
Objectives: Determine if workload; as measured by number of days rest between outings, innings pitched, batters faced, and being a starting pitcher; associates with risk for internal impingement in professional baseball pitchers. Methods: All professional baseball pitchers who were diagnosed with internal impingement between 2011-2017 were identified using the major league baseball (MLB) Health and Injury Tracking System (HITS). A separate player usage dataset was used to determine workload. We then compared workload variables between pitcher-games 2, 6, 12, and >12 weeks prior to documented internal impingement and pitcher games from a control group who were never diagnosed with internal impingement. In a paired analysis, we compared the acute workload (2, 6, 12 weeks) prior to injury and the injured pitcher's workload >12 weeks prior to injury. Results: There were 624 pitchers who suffered from internal impingement in professional baseball. Across all time points, players with more innings pitched per game, more batters faced per game, and fewer days rest in between games were associated with a subsequent internal impingement compared to controls. Pitchers who threw four or more innings per game had a 1.3-fold increase in percent of players with subsequent internal impingement compared to pitchers who threw only one inning per game. Significantly more starting pitchers were diagnosed with internal impingement over multiple time points compared to controls. Conclusions: Greater pitcher workload was associated with increased risk for internal impingement in professional baseball players. Throwing four or more innings per game increase a pitcher's risk for internal impingement 1.3-fold compared to pitchers who threw one inning per game. Starting pitchers are more likely to sustain a LD/TM tear than control pitchers.